Interference Resolution in Nonfluent Variant Primary Progressive Aphasia: Evidence From a Picture–Word Interference Task. Issue 1 (3rd March 2021) - Andreou, Maria; Peristeri, Eleni
Abstract : Background: Picture–word interference tasks have been used to investigate (a) the time course of lexical access in individuals with primary progressive aphasia (PPA) and (b) how these individuals resolve competition during lexical selection. Objective: To investigate the time course of Greek-speaking individuals with PPA to produce grammatical gender-marked determiner phrases by examining their picture-naming latencies in the context of distractor words. Method: Eight individuals with nonfluent variant PPA (nfv-PPA; M age = 62.8 years) and eight cognitively intact controls (M age = 61.1 years) participated in our study. In a picture–word interference task, the study participants named depicted objects by producing determiner + noun sequences. Interference was generated by manipulating the grammatical gender of the depicted objects and distractor words. Two stimulus onset asynchronies were used: +200 ms and +400 ms. Results: The individuals with nfv-PPA exhibited longer picture-naming latencies than the controls ( P = 0.003). The controls exhibited interference from incongruent distractors at both asynchronies ( P < 0.001); the individuals with PPA exhibited interference from incongruent distractors only at the +400-ms interval ( P = 0.002). The gender-congruency effect was stronger for the individuals with PPA than for the controls at the +400-ms interval ( P = 0.05); the opposite pattern was observed at the +200-ms interval ( P = 0.024). Conclusion: Gender interference resolution was abnormal in the individuals with nfv-PPA. The results point to deficits in lexicosyntactic networks that compromised the time course of picture-naming production.